1987
DOI: 10.1021/jf00076a022
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid glycosides of Spartan apple peel

Abstract: The flavonoid glycosides of Spartan apples were isolated by column chromatography on polyamide and Sephadex resins and by RP-HPLC. They were characterized by and 13C NMR as phlorizin and the following glycosides of quercetin: -L-arabinofuranoside, d-D-galactopyranoside, /3-D-glucopyranoside, -L-rhamnopyranoside, /3-D-xylopyranoside. The coupling constants in the XH NMR spectra were used to establish anomeric configurations of all glycosides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 6 publications
7
35
0
Order By: Relevance
“…catechins and procyanidins (Monties, 1968;Oleszeck et al, 1988). Other classes such as flavonols (Monties, 1968;Teuber and Herrmann, 1978;Dick et al, 1987) and dihydrochalcones have been found. In the latter case, phloridzin and phloretin-xyloglucoside have been identified (Oleszek et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…catechins and procyanidins (Monties, 1968;Oleszeck et al, 1988). Other classes such as flavonols (Monties, 1968;Teuber and Herrmann, 1978;Dick et al, 1987) and dihydrochalcones have been found. In the latter case, phloridzin and phloretin-xyloglucoside have been identified (Oleszek et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Previous papers have reported on the chemical composition of apple varieties from the USA and from Europe, identifying the main components as esters of caffeic and coumaric acids, procyanidines and flavonols (quercetin glycosylated derivatives). [3][4][5][6][7][8][9][10] In recent years, an increasing number of publications have reported the chemistry of flavonols, especially in view of their biological (antibacterial, antiviral, anti-inflammatory, anti-allergic, anti-trombotic, vasodilatory, anti-mutagenic and neoplastic) properties and their ability to protect against or inhibit the development of cancer when consumed on a regular basis. 11 Notwithstanding the data available from apple samples cultivated in the Northern hemisphere, it must be pointed out that the production of flavonols may vary in response to different environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…11 In addition to quercetin glycosides and floridzin and phloretin glycosides was detected in the spartan and greening apple bark. 12,13 Four anthocyanins, three quercetins, two phenolic acids, two flavan 3-ols and one dihydrochalcone glycoside were found in the apple variety of Skugog.…”
Section: Discussionmentioning
confidence: 99%